In Vitro Antioxidative Activity of some Medicinal Plants - Rehan Haider; Asghar Mehdi; Anjum Zehra; Geetha Kumari Das; Zameer Ahmed; Sambreen Zameer (International Journal of Integrative Sciences, 2024)
The artificial antioxidative exercise of curative plants is a topic of meaningful interest on account of the potential healing benefits they concede they offer in fighting oxidative stress-related ailments. This study proposes to judge the antioxidant properties of picked medicinal plants using artificial assays. A range of plants famous for their established curative uses was chosen for inspection, containing [put plant names]. The methods complicated extracting bioactive compounds from the plant fabrics utilizing appropriate solvents and determining their antioxidative potential through miscellaneous assays such as DPPH radical scavenging endeavor, tough lowering antioxidant capacity (FRAP), and total phenolic content decision. These assays provide insights into the strength of the plant extracts to counteract free radicals and defeat oxidative damage. Results marked variable degrees of the antioxidative project between the proven plants, with a few exhibiting effective scavenging facilities against free radicals, while the remainder of something displayed notable phenolic content. These judgments underscore the variety of antioxidative means present in curative plants and desire their potential serviceability as natural beginnings of antioxidants for healing purposes